The web: a thing of the past, or here to stay? - Sembhoo, Sanjay; Rasoanindrainy, Andrianjafy; Addom, Benjamin K. (Technical Centre for Agricultural and Rural Cooperation, 2015)
How relevant and useful are web tools for ICT4Ag today? Are they on their way out, or on the contrary, is the web a nucleus from which other channels spread?